2016
DOI: 10.1002/etc.3494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of trace metal accumulation in different tissues of potential bioindicator organisms: Macrobenthic filter feeders Styela plicata, Sabella spallanzanii, and Mytilus galloprovincialis

Abstract: Trace metal concentrations were measured in different tissues of Sabella spallanzanii, Styela plicata, and Mytilus galloprovincialis collected in the Termini Imerese Harbor (Sicily, Italy) to evaluate the potential use of these species as bioindicators. Higher bioaccumulation factors (BAFs) were calculated in the tube of S. spallanzanii, except for As, which had a higher BAF in the branchial crown of the same species. Regarding the other species analyzed, higher BAFs were found in the digestive gland of M. gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
4
15
1
Order By: Relevance
“…Comparable Hg concentrations have been found previously in the same tissues of S. plicata collected in the harbor of Termini Imerese, Sicily (Bellante et al, 2016). These concentrations were lower than those found in tissues of M. galloprovincialis and S. spallanzanii collected in the same study area (Bellante et al, 2016). Trace metal concentrations in D. Parrinello et al Ecotoxicology and Environmental Safety 136 (2017) 126-134 organism tissues are the result of metabolically available accumulated metal and the concentration of metal in its detoxified form (Rainbow, 2002).…”
Section: Bioaccumulation Of Mercurysupporting
confidence: 82%
See 2 more Smart Citations
“…Comparable Hg concentrations have been found previously in the same tissues of S. plicata collected in the harbor of Termini Imerese, Sicily (Bellante et al, 2016). These concentrations were lower than those found in tissues of M. galloprovincialis and S. spallanzanii collected in the same study area (Bellante et al, 2016). Trace metal concentrations in D. Parrinello et al Ecotoxicology and Environmental Safety 136 (2017) 126-134 organism tissues are the result of metabolically available accumulated metal and the concentration of metal in its detoxified form (Rainbow, 2002).…”
Section: Bioaccumulation Of Mercurysupporting
confidence: 82%
“…take place predominantly in the branchial basket, it is not surprising that the accumulation of metals could be higher in this tissue. Comparable Hg concentrations have been found previously in the same tissues of S. plicata collected in the harbor of Termini Imerese, Sicily (Bellante et al, 2016). These concentrations were lower than those found in tissues of M. galloprovincialis and S. spallanzanii collected in the same study area (Bellante et al, 2016).…”
Section: Bioaccumulation Of Mercurysupporting
confidence: 54%
See 1 more Smart Citation
“…Benthic organisms are used as indicators of oceanographic conditions, and also to monitor natural ecosystems or those affected by anthropogenic factors. A large number of studies in the literature show how benthic macroinvertebrates have been identified as excellent bioindicator species due to a number of their features (Bellante et al 2016;Parrinello et al 2017). Thanks to their long life cycle, they can track changes and pollutants, and they show sensitivity to various chemical or hydromorphological stress over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is primarily focussed on the tubiculus species Sabella spallanzanii, which was selected based on its capacity to bioaccumulate a wide spectrum of trace elements (Bocchetti et al, 2004;Fattorini and Regoli, 2012;Bellante et al, 2016) and because its structure consists of soft tissues filled in a mineralised tube of lithogenic particles cemented by organic mucus. Moreover, S. spallanzanii implements a series of adaptive responses to chemical and environmental stress and is therefore considered a good bio-indicator for environmental monitoring (Gerhardt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%